A New Approach to Fixed Point Results in Triangular Intuitionistic Fuzzy Metric Spaces - N. Hussain; S. Khaleghizadeh; P. Salimi; Afrah A. N. Abdou (Abstract and Applied Analysis)
The aim of this paper is to propose some fixed point theorems in complete parametric metric spaces. Using these theorems, we deduce as corollaries the recent results of Ionescu et al. Moreover, we suggest some new contractions and prove certain fixed point theorems in triangular intuitionistic fuzzy metric spaces. We also discuss some illustrative examples to highlight the realized improvements.